2012
DOI: 10.4161/adna.20777
|View full text |Cite
|
Sign up to set email alerts
|

Peptide nucleic acids tagged with four lysine residues for amperometric genosensors

Abstract: A homothymine PNA decamer bearing four lysine residues has been synthesized as a probe for the development of amperometric sensors. On one hand, the four amino groups introduced make this derivative nine times more soluble than the corresponding homothymine PNA decamer and, on the other hand, allow the stable anchoring of this molecule on Au nanostructured surface through the terminal -NH2 moieties. In particular, XPS and electrochemical investigations performed with hexylamine, as a model molecule, indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…One of them includes chemical modifications of the PNA backbone to increase PNA hydrophilicity (see the section on PNA modifications, e.g., the compound number 6 or 7, Figure 3). Another strategy is based on the conjugation of a PNA oligomer to positively charged amino acids at the PNA terminus [103,104]. An alternative is combining PNA with molecules capable of penetrating bacterial cells, which act as PNA transporters (Figure 5).…”
Section: Delivery Of Pna To Bacteriamentioning
confidence: 99%
“…One of them includes chemical modifications of the PNA backbone to increase PNA hydrophilicity (see the section on PNA modifications, e.g., the compound number 6 or 7, Figure 3). Another strategy is based on the conjugation of a PNA oligomer to positively charged amino acids at the PNA terminus [103,104]. An alternative is combining PNA with molecules capable of penetrating bacterial cells, which act as PNA transporters (Figure 5).…”
Section: Delivery Of Pna To Bacteriamentioning
confidence: 99%
“…PNAs tagged with four lysine residues can be developed as amperometric genosensors. The use of a nanostructured surface as the substrate for the sensor assembly results in the selective recognition of the target oligonucleotide sequence with high sensitivity . Similarly, anion‐exchanged nanosolid support with poly((2‐diethylamino)ethyl methacrylate)‐grafted cationic magnetite nanoparticle was used for the detection of DNA sequences by employing PNA probe .…”
Section: Applicationsmentioning
confidence: 99%
“…The use of a nanostructured surface as the substrate for the sensor assembly results in the selective recognition of the target oligonucleotide sequence with high sensitivity. [113] Similarly, anion-exchanged nanosolid support with poly((2-diethylamino)ethyl methacrylate)-grafted cationic magnetite nanoparticle was used for the detection of DNA sequences by employing PNA probe. [114] Peptide nucleic acids also find application as reversible switches in a DNA rotaxane architecture.…”
Section: Nanotechnologymentioning
confidence: 99%
“…Alternatively, PNA strands have been immobilized by affinity via the biotin / avidin system [36,[38][39][40][41] or by conjugation to carboxyl-terminated SAMs [42,43]. We have also shown that appending four lysine residues to the C-terminus of the homothymine decamer enabled the formation of a dense and stable layer of PNA molecules at the surface of a gold electrode nanostructured with gold nanoparticles by formation of Au-N bonds [44,45] For this work, we devised a more general immobilization strategy making use of the single primary amine function located at the pseudo 5' terminus (NH 2 -terminus) of the PNA molecule and of an appropriate bifunctional linker able to connect the PNA t 10 to the Au surface [37] (Scheme 1).…”
Section: Insert Figmentioning
confidence: 99%